Start and turn performances of elite sprinters at the 2016 European Championships in swimming - Morais, Jorge (2020)
The aim of this study was to examine the performance characteristics of male and female finalists in the 100-m distance at the 2016 European Championships in swimming (long-course-metre). The performances of all 64 (32-males and 32-females) were analysed (8 swimmers per event; Freestyle, Backstroke, Breaststroke and Butterfly). A set of start and turn parameters were analysed. In the start main outcome, male swimmers were faster in Butterfly (5.71 ± 0.14s) and females in Freestyle (6.68 ± 0.28s). In the turn main outcome, male and female swimmers were faster in Freestyle (males: 9.55 ± 0.13s; females: 10.78 ± 0.28s). A significant and strong stroke effect was noted in the start and turn main outcome, in both sexes. In the start plus the turn combined, males and females were faster in Freestyle (males: 15.40 ± 0.20s; females: 17.45 ± 0.54s). The start and the turn combined accounted almost one-third of the total race time in all events, and non-significant differences (p > 0.05) were noted across the four swim strokes. Once this research made evident the high relevance of start and turns, it is suggested that coaches and swimmers should dedicate an expressive portion of the training perfecting these actions.